Quantitative trait loci for resistance to Haemonchus contortus artificial challenge in Red Maasai and Dorper sheep of East Africa - Marshall, Karen; Mugambi, J.M.M.; Nagda, S.M.; Sonstegard, T.S.; Tassell, C.P. van; Baker, R.L.; Gibson, John P. (Wiley, 2013)
A genome-wide scan was performed to detect quantitative trait loci (QTL) for resistance to the gastrointestinal nematode Haemonchus contortus in a double backcross population of Red Maasai and Dorper sheep. The mapping population comprised six sire families, with 1026 lambs in total. The lambs were artificially challenged with H. contortus at about 6.5 months of age, and nine phenotypes were measured: fecal egg count, packed cell volume decline, two weight traits and five worm traits. A subset of the population (342 lambs) was selectively genotyped for 172 microsatellite loci covering 25 of the 26 autosomes. QTL mapping was performed for models which assumed that the QTL alleles were either fixed or segregating within each breed, combined with models with only an additive QTL effect fitted or both additive and dominance QTL effects fitted. Overall, QTL significant at the 1% chromosome-wide level were identified for 22 combinations of trait and chromosome. Of particular interest are a region of chromosome 26 with putative QTL for all nine traits and a region of chromosome 2 with putative QTL for three traits. Favorable QTL alleles for disease resistance originated in both the Red Maasai and Dorper breeds, were not always fixed within breed and had significant dominance effects in some cases. We anticipate that this study, in combination with follow-up work and other relevant studies, will help elucidate the biology of disease resistance.